"It Was Hard, and It Still Is . . .": Women of Color Navigating HSI STEM Transfer Pathways - Felisha A. Herrera; Victoria C. Rodriguez-Operana; Gabriela Kovats Sánchez; Aileen Cerrillos; Briana Marquez (SAGE Publishing, 2022)
Women of color (WOC) continue to be underrepresented in the fields of science, technology, engineering, and mathematics (STEM), where they often experience racism and sexism within disciplinary contexts that have historically privileged men and Whiteness. Participant narratives gained through focus-group and follow-up interviews illuminate the racialized and gendered STEM transfer experiences of 21 WOC who attended 2- and 4-year Hispanic-Serving Institutions (HSIs). Using a multidimensional intersectional approach, we explore the interplay between the complex identity experiences of WOC and the dynamic intersections of their transfer pathways across 2- and 4-year HSIs and within STEM disciplinary contexts. Findings underscore the inequities that continue to pervade STEM and highlight opportunities for transforming disciplinary and institutional cultures, particularly within HSI STEM transfer pathways, where there is great potential for these diverse institutions to support, validate, and benefit from the unique contributions of WOC.